Pelaksanaan Program Corporate Social Responsibility (CSR) dan Persepsi Masyarakat Asli Suku Wate: Studi Kasus PT. Kristalin Ekalestari di Kampung Nifasi, Kabupaten Nabire - Julio Marco Felix Woromboni; Irja Tobawan Simbiak; Marsal Arung Lamba (Journal of Creative Student Research, 2026)
PT. Kristalin Ekalestari, a gold mining company in Nifasi Village, Makimi District, Nabire Regency, has implemented a Corporate Social Responsibility (CSR) program for the Wate Indigenous Community since 2007. This study maps the company’s CSR program and analyzes community perceptions across three dimensions: quality, impact, and service. Data were collected through in-depth interviews with three key informants, structured interviews with nine RT heads, and questionnaires from 56 respondents. The study identified 17 CSR programs across five categories from 2007 to 2023. Regarding distribution, CSR has not reached the Mamai and Nusi Hamlets, while RT 05 and RT 06 received only minimal direct benefits. Perception-wise, 57.1% of RT heads reported dissatisfaction with the Traditional Leaders’ role in distributing CSR. Likert Scale analysis showed that impact was in the Good category (65.7%), while quality (55.4%) and service (47.1%) were in the Sufficient category. Median analysis supports these findings: quality and service recorded a median of 2 (Disagree), while impact remained positive at 4 (Agree). These results indicate an uneven and inconsistent distribution of CSR in Nifasi Village. Improved transparency regarding program distribution and coverage is still needed.